Computational Evaluation of Amorphous Carbon Coating for Durable Silicon Anodes for Lithium-Ion Batteries - Hwang, Jeongwoon; Ihm, Jisoon; Lee, Kwang-Ryeol; Kim, Seungchul (MDPI, 2015)
We investigate the structural, mechanical, and electronic properties of graphite-like amorphous carbon coating on bulky silicon to examine whether it can improve the durability of the silicon anodes of lithium-ion batteries using molecular dynamics simulations and ab-initio electronic structure calculations. Structural models of carbon coating are constructed using molecular dynamics simulations of atomic carbon deposition with low incident energies (1-16 eV). As the incident energy decreases, the ratio of sp(2) carbons increases, that of sp(3) decreases, and the carbon films become more porous. The films prepared with very low incident energy contain lithium-ion conducting channels. Also, those films are electrically conductive to supplement the poor conductivity of silicon and can restore their structure after large deformation to accommodate the volume change during the operations. As a result of this study, we suggest that graphite-like porous carbon coating on silicon will extend the lifetime of the silicon anodes of lithium-ion batteries.
Keywords: COATED SILICON; MOLECULAR-DYNAMICS; SI; LI; PERFORMANCE; FILM; NANOCOMPOSITES; PYROLYSIS; GRAPHENE; STORAGE